Implementasi Pelaksanaan Ujian Sekolah Berbasis Komputer (USBK) - Zekmana, Benni; Muhaimin, Muhaimin; Hamidah, Afreni (JOEAI (Journal of Education and Instruction), 2021)
This study aims to describe or describe the stages and processes of implementing the Computer-Based School Examination (USBK) describing and explaining how the implementation of the Computer-Based School Exam, describing and analyzing the success rate of implementing the Computer-Based School Exam, describing the obstacles in the implementation of the Computer-Based School Exam in Indonesia. SMPN 5 Sungai Penuh City. This research method is a qualitative method with the type of case study research. The design of this research uses informants, namely principals, teachers, students and USBK operators. Teacher participants who teach in the classroom can be seen from the demographic data of participants in the form of gender, years of service, education level. USBK Research Results have a good impact on teachers, schools, and students. For teachers, by using a computer, it is easier to correct students' test results. For the USBK school, it helps to determine the quality and quality of school education and understanding of student learning materials, then students can increase their self-confidence and the value of honesty and transparency in the implementation of the exam. As well as being able to help students in understanding Technology, Conclusions, USBK is an alternative technology-based exam that makes it easy for all parties involved in the evaluation of student learning, the implementation of USBK at SMP N 5 Sungai Penuh City is running smoothly and has been well prepared by the school regarding the necessary facilities and infrastructure. Keywords: Implementation, Computer Based School Exam (USBK)